The Pseudomonas aeruginosa Lectin LecB Causes Integrin Internalization and Inhibits Epithelial Wound Healing - Thuenauer, Roland (mBio, 2020)
The opportunistic bacterium Pseudomonas aeruginosa produces the fucose-specific lectin LecB, which has been identified as a virulence factor. LecB has a tetrameric structure with four opposing binding sites and has been shown to act as a cross-linker. Here, we demonstrate that LecB strongly binds to the glycosylated moieties of β1-integrins on the basolateral plasma membrane of epithelial cells and causes rapid integrin endocytosis. Whereas internalized integrins were degraded via a lysosomal pathway, washout of LecB restored integrin cell surface localization, thus indicating a specific and direct action of LecB on integrins to bring about their endocytosis. Interestingly, LecB was able to trigger uptake of active and inactive β1-integrins and also of complete α3β1-integrin–laminin complexes. We provide a mechanistic explanation for this unique endocytic process by showing that LecB has the additional ability to recognize fucose-bearing glycosphingolipids and causes the formation of membrane invaginations on giant unilamellar vesicles. In cells, LecB recruited integrins to these invaginations by cross-linking integrins and glycosphingolipids. In epithelial wound healing assays, LecB specifically cleared integrins from the surface of cells located at the wound edge and blocked cell migration and wound healing in a dose-dependent manner. Moreover, the wild-type P. aeruginosa strain PAO1 was able to loosen cell-substrate adhesion in order to crawl underneath exposed cells, whereas knockout of LecB significantly reduced crawling events. Based on these results, we suggest that LecB has a role in disseminating bacteria along the cell-basement membrane interface.